Australians’ willingness to change their discretionary food intake: findings from the CSIRO junk food analyser - Mauch, Chelsea E.; Brindal, Emily; Hendrie, Gilly A. (Frontiers in Public Health, 2024)
The overconsumption of energy dense, nutrient poor foods and beverages is a major problem globally. This study describes what and how Australian adults are willing to change in terms of their discretionary food and beverage intake. The cross-sectional study uses data from the CSIRO Junk Food Analyser online tool, which contains short questions on discretionary food and beverage consumption, and items relating to stage of change, willingness to change and dietary strategies for reducing discretionary food and beverage intake. The analysis includes 41,109 eligible Australian adults who completed the CSIRO Junk Food Analyser in the 10 weeks after launch in April 2021, with results focusing on participants exceeding dietary guidelines for discretionary food and beverage intake (67.4%, 27,694/41,109). These participants were mostly female (71.2%) and aged 31-70 years (78.4%). Forty percent reported actively trying to reduce intake of their highest ranked category of discretionary food and beverages. Willingness to change intake was lowest for alcohol (median, IQR of 3, 2:4 out of 5) and highest for takeaway foods and savoury pastries (both 4, 4:5). Almost half of the participants were willing to try 'having a few days off per week' (46.0%), while only 13.4% were willing to try to 'eliminate' their highest ranked category. Australian adults are willing to reduce their discretionary food and beverage intake, but we found that simply targeting the foods and beverages consumed most may not be the best place to start. Messages encouraging days off frequently consumed discretionary foods and beverages may be well received. Health Strategy setting the ambitious target to reduce the proportion of energy from discretionary foods and beverages to less than 20% by 2030.(8)